A study on determination moment of inertia of regular-shaped body using trifilar torsional pendulum - Mohd Noor Zakuan, Rosman (2013)
The aim of this project is to study of the Trifilar Torsional Pendulum for the experimental determination of moment of inertia for a regular-shaped body. This is seen as a method that can be improved by adding computer communication ability to this apparatus. Given a rigid body and its mass, this method allows measuring moment of inertia with only a simple single test. Software is implanted in this experiment in order to record the data and calculate all the parameters that needed for determine the moment of inertia. The motion of the pendulum is recorded. by accelerometer and transferred to the computer using microcontroller which is arduino. Then the transferred data will be displayed and calculated by the LabView. In this paper, only one type of the test object is used which is solid bar of cylinder. For the final step is comparison of the experimental result with the theoretical result.